Assassinio nella Cattedrale de Pizzetti :le retour du religieux sur la scène musicale italienne des années 1950 - Walter Zidaric (Revue LISA)
When he began setting T.-S. Eliot’s play to music as Assassinio nella Cattedrale in the second half of the 1950’s, Pizzetti was already of a respectable age and had nothing left to prove in musical composition and drama. He shared with Eliot a passion for Dante’s poetry, but Bishop Bell’s commission for Eliot’s play in 1934 coincided with the poet’s accepting a new social role as a consequence of his conversion to Anglicanism. Pizzetti’s opera is a Literaturoper inspired by the theme of religiosity and Love, religious faith appearing as a privileged area of the human experience from which Art is to benefit. Pizzetti’s artistic ethics embrace ritual and the mystery of a religious service and his outlook contrasts sharply with the economic boom of the 1950s.